Report of Macroparasites of the Invasive Fish, Cyprinus carpio, in Patagonia, Argentina - Waicheim, María Agustina (2014)
The common carp (Cyprinus carpio L.) is probably the most widely distributed freshwater fish species and is cultured on almost all continents. In South America, studies on the parasites from C. carpio are limited. The aim of the present study was to report on the macroparasites from wild C. carpio populations inhabiting the Neuquen River, which is at the southernmost distribution of C. carpio in Argentina. From spring 2011 to winter 2012, four seasonal samples of C. carpio were collected from the Neuquen River at the Ingeniero Ballester dam using gill nets. Fish were dissected and all organs were examined using microscopy. All macroparasites were determined and counted and their prevalences and mean intensities calculated. In total, 33 fish were examined and the following six parasites were recorded: the monogeneans Dactylogyrus extensus (gills) and Pseudacolpenteron sp. (in the canals of the scales along the lateral line system); the cestode Bothriocephalus sp. (intestine); the nematode Contracaecum sp. (liver and visceral fat); and the acanthocephalans Pomphorhynchus patagonicus (intestine and liver) and Polymorphus sp. (liver and wall of intestine). The monogenean D. extensus was the most commonly encountered species and had the highest prevalence and mean intensity of all parasites detected. This study reports 6 new records of parasite species in C. carpio from Argentina.